“Taiga” and “River” Components in the Nanai Socio-Tribal Organization at Lake Bolon, the Lower Amur - O. V. Maltseva; О. В. Мальцева (Archaeology, Ethnology & Anthropology of Eurasia, 2019)
This study explores the socio-tribal organization of the Nanai living near Lake Bolon, with reference to environment and migration, using published and unpublished sources, S.K. Patkanov’s statistical materials, and our field data. We employ D.N. Anuchin’s spatial distribution and variation method for reconstructing the settlement pattern and assessing the socio-tribal structure with regard to the contacts between sedentary and nomadic populations. The Lake Bolon area is a transit territory traversed by reindeer herders and hunters on their way to the Pacifi c coast, and the place from whence the Amur natives migrated in various directions. This is where the herding, hunting, and fi shing traditions merged. The Nanai settlers selected places that matched their economic specialization, and these places eventually acquired symbolic functions. Small populations merged, adapted, and borrowed the names of large territorial groups. Marital contacts and kinship ties are analyzed in detail. Social relationships were regulated by the Dokha institute: clans concluded alliances based on mutual aid. Intermarriage was allowed only after several generations. The analysis of exogamous clans such as Hodzher, Odzyal, Kileh, and Beldy, which had settled near the lake, and the interviewing of the natives suggest that along with the Tungus patrilineal kinship, the matrilineal system predating the Tungus expansion was still practiced. В статье рассматривается социально-родовая организация коренного населения долины оз. Болонь в контексте природных особенностей района и миграционных процессов в Нижнем Приамурье. Работа основана на опубликованных и неопубликованных источниках, статистических материалах С.К. Патканова, авторских полевых данных. Исследование проведено с использованием подхода пространственного распределения и изменчивости признаков, разработанного Д.Н. Анучиным, что позволило реконструировать поселенческую систему и определить социально-родовой состав населения в районе оз. Болонь. Раскрыта специфика ...